Edukasi menumbuhkan kesadaran ilmiah sejak dini: mengapa ilmu itu penting melalui penyuluhan di sd it x bandar lampung - Anang Fariz Akbar; Muhamad Fajar Dismawan; Amin Hasanuddin; Hardiansyah Hardiansyah; Mirwan Saputra; Dimas Yulian Putra; Riswandi Riswandi; Muhammad Nurwahidin (Didaktika Dwija Indria, 2026)
Scientific awareness is an essential foundation that should be developed from an early age to support students’ ability to think logically, critically, and rationally. This study aims to describe the implementation and outcomes of an educational counseling activity designed to foster scientific awareness among elementary school students. The research employed a qualitative descriptive approach using an educational counseling method conducted at SD IT X Bandar Lampung. The participants consisted of 23 sixth-grade students selected through purposive sampling. Data were collected through classroom observation, documentation, analysis of group work, and students’ written reflections. The results indicate that the counseling activities, which were structured systematically and delivered through interactive and contextual learning stages, positively influenced students’ understanding of the meaning and importance of knowledge, encouraged the development of scientific attitudes such as curiosity and confidence in expressing ideas, and increased active participation during learning activities. Furthermore, group work and reflection outcomes show that students were able to relate scientific concepts to everyday life situations in a simple and meaningful way. These findings suggest that educational counseling can serve as an effective alternative strategy to cultivate scientific awareness from an early stage in elementary education.